Effort Estimation of Business Process Modeling through Clustering Techniques - Baiao, Fernanda; Revoredo, Kate; Silveira, Brunno; Klussmann, Felipe (Histórico da iSys - Brazilian Journal of Information Systems (SERVIDOR ANTIGO - UNIRIO), 2014)
A critical activity in project planning, especially in business process modeling (BPM) projects, is effort estimation. It involves several dimensions such as business domain complexity, team and technology characteristics, turning estimation into a difficult and inaccurate task. In order to reduce this difficulty, background knowledge about past projects is typically applied; however, it is too costly to be carried out manually. On the other hand, Data Mining enables the automatic extraction of new nontrivial and useful knowledge from existing data. This paper presents a new approach for BPM project effort estimation using data mining through clustering technique. This approach was successfully applied to real data